Direct Pb Isotopic Analysis of a Nuclear Fallout Debris Particle from the Trinity Nuclear Test. - Bellucci, J.; Snape, J.; Whitehouse, M.; Nemchin, Alexander (American Chemical Society, 2016)
The Pb isotope composition of a nuclear fallout debris particle has been directly measured in post-detonation materials produced during the Trinity nuclear test by a secondary ion mass spectrometry (SIMS) scanning ion image technique (SII). This technique permits the visual assessment of the spatial distribution of Pb and can be used to obtain full Pb isotope compositions in user-defined regions in a 70 µm × 70 µm analytical window. In conjunction with backscattered electron (BSE) and energy-dispersive spectroscopy (EDS) mapping of the same particle, the Pb measured in this fallout particle cannot be from a major phase in the precursor arkosic sand. Similarly, the Pb isotope composition of the particle is resolvable from the surrounding glass at the 2s uncertainty level (where s represents the standard deviation). The Pb isotope composition measured in the particle here is in excellent agreement with that inferred from measurements of green and red trinitite, suggesting that these types of particles are responsible for the Pb isotope compositions measured in both trinitite glasses.